2007
DOI: 10.1016/j.addr.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of drugs and macromolecules to mitochondria☆

Abstract: Mitochondria is where the bulk of the cell's ATP is produced. Mutations occur to genes coding for members of the complexes involved in energy production. Some are a result of damages to nuclear coded genes and others to mitochondrial coded genes. This review describes approaches to bring small molecules, proteins and RNA/DNA into mitochondria. The purpose is to repair damaged genes as well as to interrupt mitochondrial function including energy production, oxygen radical formation and the apoptotic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 97 publications
1
39
0
1
Order By: Relevance
“…The mitochondrial targeting signal peptide (MTS), which is necessary for targeting nuclear-encoded protein to mitochondria, is useful as a specific ligand for mitochondria 6,7 . Previous reports showed that the conjugation or direct modification of MTS permitted a macromolecule such as a protein, DNA and a liposomal nanocarrier to be delivered to mitochondria [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial targeting signal peptide (MTS), which is necessary for targeting nuclear-encoded protein to mitochondria, is useful as a specific ligand for mitochondria 6,7 . Previous reports showed that the conjugation or direct modification of MTS permitted a macromolecule such as a protein, DNA and a liposomal nanocarrier to be delivered to mitochondria [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Many researches regarding cellular uptake and endosomal escape to improve the intracellular trafficking of the carrier have been performed, because these topics are common issues in the development of drug delivery system (Miyata et al, 2012;Pack et al, 2005;Wang et al, 2012;. On the other hand, the information about mitochondrial-targeted delivery of nano carrier has been limited, although many mitochondrial deliveries for various molecules have been reported (Mukhopadhyay and Weiner, 2007;Zhang et al, 2011), especially in the case of low molecular weight drugs (D'Souza et al, 2008;James et al, 2007;Wipf et al, 2005). The use of a mitochondrial targeting signal peptide (MTS) makes it possible to selectively deliver a variety of chemicals, proteins and linear DNA to mitochondria (Asayama et al, 2006;Flierl et al, 2003;Schatz, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Inner membrane is thus embedded with many transporters which allow specific compounds with a specific ligand to reach matrix space. One of those transporters is the ATP/ADP carrier which transfers ATP out from matrix space while simultaneously allowing ADP to cross inner membrane (Mukhopadhyay et al, 2007). Mitochondrial proteins synthesized in cytosolic ribosomes are translocated into mitochondria by receptor-translocator complexes present in inner and outer membranes, which are TIM (translocator inner membrane) and TOM (translocator outer membrane)…”
Section: B Mitochondriamentioning
confidence: 99%